Perceptions of Child Care in Rural America - Kathy R. Thornburg; Michelle C. Mathews; Linda Espinosa; Jean Ispa (Journal of Research in Rural Education, 1997)
This study reports the results of an investigation into the beliefs, attitudes, and satisfaction ofrural mothers, child care providers, kindergarten teachers and employers. Data were collectedfrom J34 mothers, 55 child care providers, 46 kindergarten teachers, and 62 employers. Mothers reported that they were "very satisfied" with the quality ofchild care services they were receiving and the degree of employer support. Although the majority of child care providers had a limited infrastructure ofsupport and information, they had positive attitudes toward training, perceived relatively little stress, and were "extremely satisfied" with the amount ofsupport received. Kindergarten teachers were less optimistic and concluded that their students, as a whole, are less ready for school than students 5 years ago. Employers noted that the majority of their employees (78%) had no control over the scheduling of their work hours and that most employees (82%) had no job/family conflict. Results are analyzed and interpreted within the context ofa midwestern rural sample and Bronfenbrenner's ecological theory ofhuman development.